Aerosol Deposited Polycrystalline PbZr0.53Ti0.47O3 Thick Films with a Large Transverse Piezoelectric Coefficient - Long Teng; Juan Yang; Yongguang Xiao; Hongbo Cheng; Shibo Gong; Gao Luo; Jinlin Yang; Wenjia Zhang; Zhenwei Shen; Jun Ouyang (Crystals)
The aerosol deposition (AD) method utilizes high kinetic-energy submicron powders to impact and form a film on a substrate. It is a highly efficient deposition method, capable of producing films or coatings with a strong interfacial bonding and a dense nano-grain structure without thermal assistance. In this work, PbZr0.53Ti0.47O3 (PZT53/47) films (~1.2 μm thick) were deposited on Pt/Ti/Si(100) substrates via the AD method. After a conventional annealing process (700 °C for 1 h), these PZT53/47 films displayed a dense, crack-free, nano-grained morphology, corresponding to an optimal electrical performance. A large maximum polarization (Pmax = 70 μC/cm2) and a small coercive field (Ec = 104 kV/cm) were achieved under the maximum applicable electric field of 1.6 MV/cm. The PZT53/47 films also exhibited a large small-field dielectric constant of ~984, a high tunability of 72%, and a low leakage current of ~3.1 × 10−5 A/cm2 @ 40 V. Moreover, the transverse piezoelectric coefficient (e31.f) of these AD-processed films was as high as −4.6 C/m2, comparable to those of sputter-deposited PZT53/47 films. These high-quality PZT53/47 thick films have broad applications in piezoelectric micro-electromechanical systems.